E-learning on History learning: Aspect of material, teacher, learning environment, and student - Jamiludin Jamiludin; Darnawati Darnawati (Institute of Advanced Engineering and Science, 2022)
This research was conducted to determine the student’s perception of e-learning in studying History in terms of material, teachers, learning environment, the students themselves, and the teacher's perception of e-learning in teaching History. The researchers employed a mixed-method design. Instruments of this research were questionnaire and interview guide. The questionnaire was used to collect quantitative data while interview guide for qualitative data. The questionnaire consists four aspects: material, teacher, learning environments, and students’ view. The subjects were 25 history teachers and 161 students of senior high school in Kendari City, Indonesia. The result found that students prefer to study face-to-face. They prefer that the material is taught directly by the teacher in class. Class conditions are comfortable and they can interact with teachers and friends. Students do not feel bored doing assignments from teachers during a pandemic. They like to summarize history assignments rather than memorizing the material. Most students complain about the conditions of studying from home. Network problems and not having facilities, such as laptops and smartphones are the main problems for online learning. History teachers assume that in implementing e-learning, they prefer asynchronous e-learning. History teachers mostly use e-learning applications, such as Google Classroom, WhatsApp, and YouTube. This study was expected to shed new light on the intriguing concept of students and teacher’s perception of e-learning on history learning.